Effect of niacin supplementation on milk production and ketosis of dairy cattle - Dufva, G.; Bartley, E.; Dayton, A.; Riddell, D. (Kansas Agricultural Experiment Station, 2012)
Two lactation trials were undertaken to evaluate the effect of a niacin supplement on milk production and 'the physiological symptoms of ketosis. Blood ketone and non-esterified fatty acid levels were lower and blood glucose concentrations higher in niacin-supplemented cows. These trends were exhibited regardless of whether supplementation began 2 wk prepartum or immediately after calving. A 6 g daily dose was found to be of equal or higher benefit than a 12 g supplement. Cows gi ven niacin consistently produced more milk than controls, though the difference was small.
Keywords: Dairy; Niacin; Milk production; Ketosis